2008
DOI: 10.1113/jphysiol.2008.161943
|View full text |Cite
|
Sign up to set email alerts
|

GABA transporter 1 tunes GABAergic synaptic transmission at output neurons of the mouse neostriatum

Abstract: GABAergic medium-sized striatal output neurons (SONs) provide the principal output for the neostriatum. In vitro and in vivo data indicate that spike discharge of SONs is tightly controlled by effective synaptic inhibition. Although phasic GABAergic transmission critically depends on ambient GABA levels, the role of GABA transporters (GATs) in neostriatal GABAergic synaptic transmission is largely unknown. In the present study we aimed at elucidating the role of GAT-1 in the developing mouse neostriatum (postn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 54 publications
10
67
2
Order By: Relevance
“…Parasagittal brain slices (300 μm thick) were prepared, as described (43), from transgenic R6/2 mice and their WT (CBA × C57BL/6J) littermates (postnatal days 25-57) as described (43), and from BACHD mice and their WT littermates (FVB/N). Animals were bred and genotyped at Jackson Labs and provided by the CHDI Foundation.…”
Section: Methodsmentioning
confidence: 99%
“…Parasagittal brain slices (300 μm thick) were prepared, as described (43), from transgenic R6/2 mice and their WT (CBA × C57BL/6J) littermates (postnatal days 25-57) as described (43), and from BACHD mice and their WT littermates (FVB/N). Animals were bred and genotyped at Jackson Labs and provided by the CHDI Foundation.…”
Section: Methodsmentioning
confidence: 99%
“…Vicini's (Ade et al 2008;Janssen et al 2009;Janssen et al 2011;Luo et al 2013) and other groups (Kirmse et al 2008;Janssen et al 2009;Santhakumar et al 2010) have provided solid evidence for the presence and the developmental profile of a tonic GABA A current in MSNs. (Note, however, that one study did not find any evidence for a tonic GABA A current in D2 + or D1 + MSNs; Gertler et al 2008.)…”
Section: Striatummentioning
confidence: 96%
“…Many groups ( Ade et al, 2008 ;Kirmse et al, 2008 ;Janssen et al, 2009Janssen et al, , 2011Santhakumar et al, 2010 ;Luo et al, 2013 ) have shown the presence of a tonic GABA A current in MSNs, although one study ( Gertler et al, 2008 ) did not report a tonic GABA A current in either D2 + or D1 + MSNs. D2 + MSNs have a greater tonic GABA A current ( Zheng and Johnson, 2001 ) and are more sensitive to low doses of GABA than D1 + MSNs ( Ade et al, 2008 ).…”
Section: Striatummentioning
confidence: 99%